Experimental Establishing of Moving Hydraulic Jump in a Trapezoidal Channel - Najah K. Al-Bedyry; Maher A. A. Kadim; Saman H. Hussein; Zainab S. Al-Khafaji; Fatimah N. Al-Husseinawi (Salehan Institute of Higher Education, 2023)
This research was prepared as a preliminary laboratory study to achieve a moving hydraulic jump with controlled discharges. It is an initial part of the study that is being prepared to treat the salt tide occurring in the Shatt al-Arab due to the lack of water imports that were coming from the Karun and Karkheh rivers from Iranian territory, as this scarcity caused a salt tide that affected significantly the environmental reality of the city of Basra and the agricultural lands surrounding the Shatt al-Arab, such as the Shatt al-Arab district and the Siba orchards. As part of the proposed solutions, a moving hydraulic jump is created that pushes the salt tongue into the Persian Gulf; the results were promising. A moving hydraulic leap is a good example of unstable super- and sub-critical flow regimes and is regarded as a specific case of unsteady flow in a channel. There aren't many published experiments on this particular flow type, and the quantitative simulation of such a flow state has some inherent complexity. An experimental setup was created for this work in order to assess the hydraulic performance of a moving hydraulic jump in a trapezoidal flume. A sluice gate was installed at the flume's upstream edge to provide an unstable supercritical flow regime, movable hydraulic jumps along the channel, and temporal water stages at the gate's upstream side for the various downstream end boundary situations. Several flow factors, including energy head, pressure head, and flow depth, were estimated from the recorded data. The study found connections between discharge and shifting hydraulic jump variables. By employing relatively stable momentum and energy formulas, simple and time-independent formulas were developed that accurately predicted the pressure head in the subcritical region of an unstable mixed flow. As a result, the moving hydraulic jump factor can be correctly predicted using time-independent correlations by using the discharge variation as a boundary scenario. Doi: 10.28991/CEJ-2023-09-04-08 Full Text: PDF